THE COMPUTATIONAL INVESTIGATION OF SIXTEEN ANTIVIRAL DRUGS AGAINST MAIN PROTEASE (MPRO) AND SPIKE PROTEASE (SPRO) OF SARS-2-COV-19 - Ajoy Kumer; Unesco Chakma; Md. Tawhidul Islam; Debashis Howlader; Tomal Hossain (Journal of the Chilean Chemical Society, 2021)
In this research, the fourteen commonly used antiviral drugs were investigated through the computational tools against CoV-19 or SARS-2, as well as two small bioactive molecules from the cannabis plant, Tetrahydrocannabinol (THC) and Cannabinol (CBN). Thus, these were selelcted for molecular docking against main protein (5r7y) and spike protein (6xs6) of coronavirus. It was illustrated that the binding energies of Mpro for Pimodivir, Baloxavir Marboxil, Lopinavir, Baricitinib, Remdesivir, THC, Darunavir, Galidesivir, Nitazoxanide, CBN, Ritonavir, Penciclovir, Ribavirin, Favipiravir, Umifenovir, and Chloroquine were -8.6, -7.7, -7.6, -7.5, -7.3, -6.8, -6.6, -6.6, -6.6, -6.5, -6.5, -6.3, -6.2, -6.0, -5.7 and -5.4 kcal/mol, respectively, which could be supported for good binding molecules against micropathogens, where it was -9.8, -6.9, -6.9, -7.1, -7.1, -7.1, -7.5, -6.0, -6.2, -7.4, -5.8, -5.9, -5.7, -5.6 and 5.4, respectively, for Spro. Among these, Pimodivir is a best-bonded molecule with Mpro and Spro in view of molecular docking score. Secondly, the ligand interaction was accounted for this protein against required corona virus protein consisting of weak H bonding, hydrophobic bond and Van dar Waal interaction. For justification of molecular docking, the molecular dynamics was calculated for top six scored drugs where the root mean square deviation(RMSD) and root mean square fluctuation (RMSF) were showed that the six drugs for both main protein and spike protein.  Additionally, the chemical hardness and softness have calculated, and the lowest value of softness has found in sample 06 and 13 around 0.24. The HOMO-LUMO gap has calculated with a different value for all, but the lowest value has obtained for 01. Finally, the pharmacokinetics and Lipisinki rule were calculated, and all of these molecules had satisfied the Lipisinki rule. Finally, using the admetsar online data base, absorption, distribution, metabolism, excretion and toxicity have calculated.